Deafhood: a concept in formation in the field of Deaf Studies in Brazil - Fernandes, Sueli de Fátima (2019)
Deaf Studies within the Education is a recent research field whose object is the study of linguistic and cultural differences of Deaf communities, by problematising the historic colonial narrative imposed on the Deaf from a supposed hearing normality. The concept of Deafhood, defined by Paddy Ladd, preeminent British researcher and activist, covers multiple contributions to the field by problematising the dominant representation systems about identity(ies), difference, alterity, power relations and the effects of such approach in educational processes. The bibliographical research methodology used nine Paddy Ladd works, not yet published in Brazil, with the aim of proposing a discussion about the concept of Deafhood and its potential contribution to the linguistic and cultural rights of the Deaf. Deafhood proves itself to be a powerful overarching conceptual tool anchored at the power relations among hearing and Deaf peoples, capable to inform both the political and academic spheres. It is widely adopted in the studies of acclaimed Deaf and hearing Brazilian intellectuals. Its centrality of the denouncement of audiology as an expression of hearing colonialism brings about important reflections to inform a Deaf epistemology that is centered in the production of subaltern Deaf researchers and on the dynamic and multifaceted cultural productions of the Deaf communities. The works by Paddy Ladd used in this research offer original contributions to the framing of inquiries the hegemonic colonialist discourses and practices by acting on the displacement of the discourses that mobilize the field of Deaf Studies and by strengthening the political mobilisation to guarantee linguistic rights for the Deaf in the national context.